Effect of Phaleria macrocarpa Extract on NF-KB, MMP-2, and MMP-9 Expression in Endometriosis Mice Model - Annissa Febriani; Sutrisno Sutrisno; Yahya Irwanto; Irfani Baihaqi; I Wayan Arsana Wiyasa; Bambang Rahardjo (Asian Journal of Health Research, 2022)
Introduction: Endometriosis is the most common disease that affects the reproductive health and function of women of reproductive age. Treatment for endometriosis includes surgery and medication. Phaleria macrocarpa is a plant native to Indonesia that contains bioactive fractions known to have antiproliferative and apoptotic effects. Therefore, this study aimed to evaluate the effect of Phaleria macrocarpa extract on matrix metalloproteinases (MMP-2 and MMP-9) and NF-KB expression in the endometriosis mice model (Mus musculus). Methods: This study used a Randomized Post-Test Only with Control Group Design. Involves six groups, namely a negative control group (healthy mice without flavonoids from Phaleria macrocarpa fruit extract), a positive control group (an endometriosis model without being given flavonoids from Phaleria macrocarpa fruit extract), and a treatment group, namely a group given four different doses of flavonoids from Phaleria macrocarpa fruit extract: 3.75 milligrams per day, 7.5 milligrams per day, 11.25 milligrams per day and 15 milligrams per day. expressions of NF-KB, MMP-2, and MMP-9 were seen using Immunohistochemistry staining and observed under a microscope with 40x magnification. The data collection used an immunoratio technique with ImageJ analysis software. Furthermore, data analysis using the one-way ANOVA method. Results: In this study, the treatment group with four different doses of Phaleria macrocarpa extract could reduce the expression of MMP-2, MMP-9, and NF-KB. Groups with higher doses of Phaleria macrocarpa extract showed lessen of MMP-2, MMP-9, and NF-KB expression. Conclusion: In the endometriosis mice model, Phaleria macrocarpa fruit can reduce NF-KB, MMP-2, and MMP-9 expression.